Predicting the number of Tishreen University graduates using exponential smoothing during the period (1979-2020) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Predicting the number of Tishreen University graduates plays an important role in proper planning for graduates, as the current study aimed to predict the number of Tishreen University graduates using the time series of the number of graduates to achieve the desired goal. Exponential smoothing was used to predict the number of Tishreen University graduates, because of its high ability to process the time series. The descriptive statistical approach was relied upon in addition to the inductive analytical approach in order to describe the study data As well as testing its hypotheses, the study concluded that the double exponential smoothing model is more efficient in forecasting because it has the lowest value for the forecast accuracy criteria, RMSE, MAE. Therefore, it was relied upon in forecasting the number of Tishreen University graduates during the next five years, because of the importance of this topic in order to know the nature of The relationship between the competencies of Tishreen University graduates and the needs of the labor market.